Self-repairing anti-termite cable
By adopting the use of covalent bonds and super molecular interactions in the cable outer sheath to form a dual network structure, the problem of scratching and lacking self -repairing capabilities during the construction process of cables is solved. Effect.
Patent Information
- Application Number
- CN202411929680.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-12-26
AI Technical Summary
Existing cables are prone to scratches during construction, resulting in breakthroughs in termite bites and affecting the anti-antit effect. At the same time, crosslinked polyethylene materials lack self-repair capabilities and are difficult to maintain performance in humid environments.
The outer sheath uses covalent bonds and supramolecular interactions to form a double network structure, including linear low-density polyethylene, high-density polyethylene, silane coupling agent, zinc oxide and anti-ant agent, through the hydrophobic thiocarbonyl groups. Hydrogen bonding and ionic bonding of zinc to carboxyl groups provide self-healing capabilities.
It realizes self-repair of cables at room temperature, improves the mechanical properties and anti-ant effect of the material, and is suitable for use in underground humid environments.
Smart Images

Figure CN119361222A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cables, and in particular relates to a self-repairing anti-ant cable. Background Art
[0002] Most cables are laid underground in cities or directly buried in the soil. This laying method can reduce the impact on ground traffic and protect cables from external physical damage, but there will be problems with rats and termites. The research on cable anti-termite has a long history. Australia conducted experiments on drug anti-termite as early as the 1830s. The drug anti-termite effect was obvious in the early stage, but the cable samples were taken back several years later to determine the toxicity, and it was found that the toxicity had decreased. This was mainly due to the aging of the plastic and the gradual release of the drug. In order to solve the problem of drug release and environmental protection caused by the aging of the drug sheath plastic, scientists at home and abroad have also explored the research on cable anti-termite from a physical perspective. The hardness is mainly used to prevent termites from biting, and the anti-termite effect is obvious. However, when the outer sheath of the cable is scratched during the construction process, it provides a breakthrough for termites to bite, thus affecting the anti-termite effect. Cross-linked polyethylene is mostly cross-linked through irreversible covalent bonds, resulting in the material not having self-repairing ability. Although there is a technology to repair cross-linked polyethylene by injecting a repair agent to react with water, there are differences in the diffusion rates of the molecules of each component of the repair liquid, and the initial position is prone to accumulation of repair liquid.
[0003] Intrinsic self-repair means that the material can achieve self-repair by using dynamic bonds in the molecular network without adding a repair agent, and the self-repair can be repeated many times. Intrinsic self-repair at room temperature is mainly based on supramolecular interactions, including hydrogen bonds, ionic bonds, and metal-ligand interactions. However, most cables are buried directly in the soil in a humid environment. Polar supramolecular interactions are easily affected by the humid environment, and the hydrogen bond network is destroyed, resulting in a decrease in the thermal and mechanical properties of the material. Summary of the invention
[0004] In order to overcome the deficiencies of the above-mentioned prior art, the present invention provides a self-repairing anti-ant cable, which adopts covalent bonds and supramolecular interactions to form a double network structure. The covalent bonds ensure the basic mechanical properties of the material, and the supramolecular interactions provide a higher self-repairing efficiency, wherein the supramolecular interactions include hydrogen bonds between hydrophobic thiocarbonyl groups and ionic bonds between zinc and carboxyl groups.
[0005] The technical solution for achieving the purpose of the present invention is as follows: A self-repairing anti-ant cable, comprising an optical fiber sensor, a conductor, a conductor shielding layer, an insulating layer, an insulating shielding layer, a communication optical cable, a filling rope, an isolation sleeve, a steel belt armor and an outer sheath, characterized in that, in parts by weight, the outer sheath comprises 50-70 parts of linear low-density polyethylene, 40-60 parts of high-density polyethylene, 0.9-1.2 parts of a silane coupling agent, 0.12-0.15 parts of an initiator, 1.8-3.0 parts of an antioxidant, 1.2-1.5 parts of a co-crosslinking agent, 1.2-1.5 parts of zinc oxide, 2.4-2.8 parts of a catalyst, and 2-3 parts of an anti-ant agent; the co-crosslinking agent has the following molecular structure of Formula I: , formula I; wherein n=1~10, R is at least one of aliphatic secondary amine or tertiary amine; the optical fiber sensor is directly implanted into the cable conductor, and can directly and accurately monitor various physical quantities of the cable operation.
[0006] Preferably, the auxiliary cross-linking agent has at least one of the following molecular structures of Formula II or Formula III: , Formula II; , Formula III.
[0007] More preferably, the auxiliary cross-linking agent has the structure of Formula II above.
[0008] Preferably, the silane coupling agent is at least one of vinyl triethoxysilane and vinyl trimethoxysilane; the initiator is dicumyl peroxide; the catalyst is dibutyltin dilaurate; and the termite repellent is at least one of n-nonanoic acid vanillamide and FYJ-01 anti-termite functional masterbatch.
[0009] More preferably, the silane coupling agent is vinyl trimethoxy silane; and the anti-termite agent is a functional masterbatch of n-nonanoic acid vanillylamide and FYJ-01 anti-termite in a mass ratio of (1-2):1.
[0010] Preferably, the physical quantities detected by the optical fiber sensor are temperature, partial discharge and stress.
[0011] Specifically, the molecular structure of formula I is obtained by the following steps: S1. At room temperature and under nitrogen protection, add N,N'-thiocarbonyldiimidazole to a reactor and add N,N-dimethylformamide to dissolve it, dissolve diaminodialkylamine in N,N-dimethylformamide and slowly add it dropwise to the reactor. After reacting for 1-2 hours, add aliphatic secondary or tertiary amine, raise the temperature to 40-60 °C, continue to react for 4-6 hours, introduce the mixture into cold water, precipitate solid, filter, wash the filter cake with cold water, and dry to obtain thiourea compound; S2. The thiourea compound obtained in step S1 is dispersed in N,N-dimethylformamide, triethylamine and tetrahydrophthalic anhydride are added, and the mixture is stirred at a temperature of 35-45°C for 12-18 hours. The reaction solution is poured into cold ethyl acetate, the precipitated solid is filtered, the filter cake is washed with ethyl acetate, and vacuum dried to obtain a molecular structure of formula I.
[0012] Preferably, in step S1, the molar ratio of N,N'-thiocarbonyldiimidazole, diaminodialkylamine and aliphatic secondary or tertiary amine is 2:1:(5-8); and the dropping time of the diaminodialkylamine is 30-60 min.
[0013] Preferably, the molar ratio of the thiourea compound, triethylamine and tetrahydrophthalic anhydride in step S2 is 1:(2-3):(1.5-2).
[0014] Preferably, a method for preparing a self-repairing anti-ant cable comprises the following steps: 1) Pre-preparation of outer sheath material: dissolve the initiator in the silane coupling agent, put the linear low-density polyethylene and high-density polyethylene into a 70-90 ℃ oven and dry them for 10-12 hours, then divide them into four equal parts, one part is mixed with the initiator and the silane coupling agent, one part is mixed with the catalyst, one part is mixed with the auxiliary cross-linking agent and the anti-termite agent, and one part is mixed with zinc oxide, and they are placed in sealed containers and left to stand for 18-24 hours, and then extruded by a twin-screw extruder in turn to obtain mixed masterbatch; 2) Outer sheath material: The mixed masterbatch is added into a preheated single screw extruder and extruded onto the steel belt armor. After cooling in a water bath, the extruded material is fixed and placed in a humid environment at a temperature of 25-40 ℃ for 3-4 days. After the self-crosslinking process of the polyethylene is completed, it is dried to obtain a self-repairing anti-ant cable.
[0015] More preferably, the parameters of the twin-screw extruder in step 1) are temperature 75-165°C and main engine speed 190-220 r / min; the parameters of the single-screw extruder in step 2) are temperature 170-210°C and main engine speed 30-40 r / min.
[0016] Beneficial Effects
[0017] The present invention has the following beneficial effects: providing a self-repairing anti-ant cable, which can self-repair at room temperature when the cable is scratched; introducing supramolecular interactions and irreversible covalent bonds at the same time, when subjected to external force, the supramolecular interactions are first broken to dissipate energy and improve the mechanical properties of the material, while the covalent bonds ensure the integrity and elasticity of the material; cross-linking polyethylene with a silane coupling agent provides better mechanical properties for the outer sheath; after zinc oxide reacts with an auxiliary cross-linking agent, the water generated can be used for internal self-cross-linking of polyethylene, and zinc and carboxyl form ionic bonds to provide an ionic dynamic cross-linking network for cross-linked polyethylene; thiocarbonyl, as a polar molecular structure, has a certain hydrophobic ability while providing hydrogen bonds, and can be suitable for underground humid environments; thiocarbonyl can coordinate with zinc, further improving the strength of the dynamic non-covalent network. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a schematic diagram of the overall structure of the self-repairing anti-ant cable of the present invention; In the figure: 100. optical fiber sensor, 200. conductor, 201. conductor shielding layer, 202. insulating layer, 203. insulating shielding layer, 204. filling rope, 205. isolation sleeve, 206. steel belt armor, 207. outer sheath, 300. communication optical cable; Figure 2 The schematic diagram of the synthesis route and structure of the cross-linking agent of the present invention; Figure 3 It is the cross-linking method of the self-repairing anti-ant cable of the present invention; Figure 4 It is the nuclear magnetic hydrogen spectrum of the cross-linking agent 1 of the present invention. DETAILED DESCRIPTION
[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] In the examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.
[0021] The raw materials and equipment used in the embodiments and comparative examples are described as follows: Vinyltrimethoxysilane: Product No. CH0020, Hubei Chenghai Chemical Co., Ltd. Linear low-density polyethylene: brand DFDA-7042, purchased from Wuhan Rongchuang Plastic Co., Ltd.; High-density polyethylene: item number 5000S, purchased from Dongguan Shenghua Plastic Raw Materials Co., Ltd.; Ethylene-octene elastomer: brand 8999, purchased from Dongguan Yucheng Plastic Chemical Co., Ltd.; Initiator: dicumyl peroxide, purchased from Nanjing Reagent; Catalyst: dibutyltin dilaurate, purchased from Kangdisi Chemical (Hubei) Co., Ltd.; Anti-ant agent 1: n-nonanoic acid vanillamide, HD-99, purchased from Qingdao Haida Chemical; Anti-termite agent 2: FYJ-01 anti-termite functional masterbatch, purchased from Shenzhen Heyanyue Plastic Pigment; N,N'-Thiocarbonyldiimidazole: Product No. S49067, purchased from Shanghai Yuanye Biotechnology Co., Ltd.; Diethylenetriamine: purchased from Shandong Xinheng Chemical Co., Ltd. Methylamine hydrochloride: purchased from Nanjing Reagent; Methylamine tetrahydrofuran solution: prepared from methylamine hydrochloride; Tetrahydrophthalic anhydride: purchased from Nanjing Oriental Pearl Industry and Trade Co., Ltd.; Stearic acid: purchased from Nantong Runfeng Petrochemical Co., Ltd. 3-Cyclohexenylcarbonyl chloride: Shanghai Baishun Biotechnology Co., Ltd.; 3-Cyclohexene-1-carboxylic acid: product number 1033333, purchased from Shanghai Haohong Biomedicine Technology.
[0022] Cross-linking agent 1: S1. At room temperature and under nitrogen protection, 2 mol of N,N'-thiocarbonyldiimidazole was added to a reaction kettle and N,N-dimethylformamide was added to dissolve it. 1 mol of diethylenetriamine was dissolved in N,N-dimethylformamide and slowly added dropwise to the reaction kettle. After reacting for 1 h, 8 mol of methylamine in tetrahydrofuran was added. The temperature was raised to 50°C and the reaction was continued for 6 h. The mixture was introduced into cold water to precipitate solids, which were filtered and the filter cake was washed with cold water and dried to obtain a thiourea compound. S2. Disperse 1 mol of the thiourea compound obtained in step S1 in N,N-dimethylformamide, add 2 mol of triethylamine and 1.8 mol of tetrahydrophthalic anhydride, stir at 40 °C for 18 h, pour the reaction solution into cold ethyl acetate, filter the precipitated solid, wash the filter cake with ethyl acetate, and vacuum dry to obtain the cross-linking agent 1.
[0023] Cross-linking agent 2: S1. At room temperature and under nitrogen protection, 2 mol of N,N'-thiocarbonyldiimidazole was added to a reaction kettle and N,N-dimethylformamide was added to dissolve it. 1 mol of diethylenetriamine was dissolved in N,N-dimethylformamide and slowly added dropwise to the reaction kettle. After reacting for 1 h, 8 mol of methylamine in tetrahydrofuran was added. The temperature was raised to 50°C and the reaction was continued for 6 h. The mixture was introduced into cold water to precipitate solids, which were filtered and the filter cake was washed with cold water and dried to obtain a thiourea compound. S2. Disperse 1 mol of the thiourea compound obtained in step S1 in N,N-dimethylformamide, add 2 mol of triethylamine and 1.8 mol of 3-cyclohexenylcarbonyl chloride, stir at 40 °C for 18 h, pour the reaction solution into cold ethyl acetate, filter the precipitated solid, wash the filter cake with ethyl acetate, and vacuum dry to obtain the cross-linking agent 2.
[0024] A method for preparing a self-repairing anti-ant cable comprises the following steps: 1) Pre-preparation of outer sheath material: dissolve the initiator in the silane coupling agent, put the linear low-density polyethylene and high-density polyethylene into an 80 ℃ oven for drying for 12 hours, and then divide them into four equal parts, one part is mixed with the initiator and the silane coupling agent, one part is mixed with the catalyst, one part is mixed with the auxiliary cross-linking agent and the anti-termite agent, and one part is mixed with zinc oxide. Put them into sealed containers and let them stand for 24 hours. Then, use a twin-screw extruder at a temperature of 75~165 ℃ and a main engine speed of 190~220 r / min to extrude and mix to obtain a mixed masterbatch; 2) Outer sheath material: The mixed masterbatch is added into a preheated single screw extruder at a temperature of 170-210 °C and a main engine speed of 30-40 r / min, and extruded onto the steel belt armor. After cooling in a water bath, the extruded material is fixed and placed in a humid environment at a temperature of 25-40 °C for 3-4 days. After the self-cross-linking process of the polyethylene is completed, it is dried to obtain a self-repairing anti-ant cable.
[0025] Table 1 Example and comparative example formula (kg)
[0026] The cross-linked polyethylene in Comparative Example 3 is not modified by carboxyl groups, and the cross-linked polyethylene in Comparative Example 4 is not modified by thiocarbonyl groups.
[0027] The following is the test method of the performance parameters involved in the present invention: 1. Anti-termite performance: The products of the embodiments and comparative examples were tested according to the standard GB / T2951.38-1986, and the moth-proofing grade was recorded; 2. Surface hardness test: The Shore hardness of the products of the embodiments and comparative examples was tested according to standard ISO 7619-1:2012-02; 3. Wear resistance test: The products of the embodiment and the comparative example were tested for wear according to the standard GB / T 5478-2008; wherein, the single arm load was 1000 g, the double-stroke impact was 20,000 times, and the wear amount was recorded; 4. Self-repair performance test: Place the outer sheath, blade and wood chip in order from bottom to top, load a 30kg weight on the wood chip, and push the wood chip from front to back to form a scratch on the surface of the outer sheath. Repair it with 1kg pressure, and use a stereo microscope to photograph and measure the scratch width before repair d1 / after repair d2: Repair efficiency = .
[0028] Table 2 Performance test of examples and comparative examples
[0029] It can be seen from the data of Examples 2 to 6 that as the mass ratio of the silane coupling agent to the co-crosslinking agent decreases, the hardness of the obtained outer sheath becomes lower and the repair efficiency gradually increases. The silane coupling agent provides irreversible covalent bonds to increase the hardness, and the supramolecular interaction improves the self-repair efficiency of the outer sheath; it can be seen from the data of Comparative Examples 1 to 2 that a mass ratio of the silane coupling agent to the co-crosslinking agent that is too large or too small will affect the performance of the outer sheath; it can be seen from the data of Comparative Examples 3 to 4 that a single supramolecular interaction is not as good as the performance effect of multiple supramolecular interactions on the hardness and self-repair efficiency of the outer sheath.
[0030] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A self-repairing anti-ant cable, comprising an optical fiber sensor, a conductor, a conductor shielding layer, an insulating layer, an insulating shielding layer, a communication optical cable, a filling rope, an isolation sleeve, a steel belt armor and an outer sheath, characterized in that: The outer sheath comprises, by weight, 50-70 parts of linear low-density polyethylene, 40-60 parts of high-density polyethylene, 0.9-1.2 parts of silane coupling agent, 0.12-0.15 parts of initiator, 1.8-3.0 parts of antioxidant, 1.2-1.5 parts of auxiliary cross-linking agent, 1.2-1.5 parts of zinc oxide, 2.4-2.8 parts of catalyst, and 2-3 parts of anti-termite agent; the auxiliary cross-linking agent has the following molecular structure of Formula I: , formula I; wherein n=1~10, R is at least one of aliphatic secondary amine or tertiary amine; the optical fiber sensor is directly implanted into the cable conductor, and can directly and accurately monitor various physical quantities of the cable operation.
2. A self-repairing anti-ant cable as claimed in claim 1, characterized in that: The auxiliary cross-linking agent has at least one of the following molecular structures: , Formula II; , Formula III.
3. A self-repairing anti-ant cable as claimed in claim 1, characterized in that: The silane coupling agent is at least one of vinyl triethoxysilane and vinyl trimethoxysilane; the initiator is dicumyl peroxide; the catalyst is dibutyltin dilaurate; and the termite repellent is at least one of n-nonanoic acid vanillamide and FYJ-01 anti-termite functional masterbatch.
4. The self-repairing anti-ant cable according to claim 1, characterized in that: The physical quantities detected by the optical fiber sensor are temperature, partial discharge and stress.
5. The self-repairing anti-ant cable according to claim 1, characterized in that: The molecular structure of formula I is obtained by the following steps: S1. At room temperature and under nitrogen protection, N,N'-thiocarbonyldiimidazole is added to a reaction kettle and N,N-dimethylformamide is added to dissolve it. Diaminodialkylamine is dissolved in N,N-dimethylformamide and slowly added dropwise to the reaction kettle. After reacting for 1-2 hours, an aliphatic secondary amine or tertiary amine is added. The temperature is raised to 40-60 °C and the reaction is continued for 4-6 hours. The mixture is introduced into cold water to precipitate a solid, which is filtered and the filter cake is washed with cold water and dried to obtain a thiourea compound. S2. The thiourea compound obtained in step S1 is dispersed in N,N-dimethylformamide, triethylamine and tetrahydrophthalic anhydride are added, and the mixture is stirred at a temperature of 35-45°C for 12-18 hours. The reaction solution is poured into cold ethyl acetate, the precipitated solid is filtered, the filter cake is washed with ethyl acetate, and vacuum dried to obtain a molecular structure of formula I.
6. A self-repairing anti-ant cable as claimed in claim 5, characterized in that: In step S1, the molar ratio of N,N'-thiocarbonyldiimidazole, diaminodialkylamine and aliphatic secondary or tertiary amine is 2:1:(5-8); the dropping time of the diaminodialkylamine is 30-60 min.
7. The self-repairing anti-ant cable according to claim 5, characterized in that: The molar ratio of the thiourea compound, triethylamine and tetrahydrophthalic anhydride in step S2 is 1:(2-3):(1.5-2).
8. The method for preparing a self-repairing anti-ant cable according to claim 1, characterized in that: The following steps are involved: 1) Pre-preparation of outer sheath material: dissolve the initiator in the silane coupling agent, put the linear low-density polyethylene and high-density polyethylene into a 70-90 ℃ oven and dry them for 10-12 hours, then divide them into four equal parts, one part is mixed with the initiator and the silane coupling agent, one part is mixed with the catalyst, one part is mixed with the auxiliary cross-linking agent and the anti-termite agent, and one part is mixed with zinc oxide, and they are placed in sealed containers and left to stand for 18-24 hours, and then extruded by a twin-screw extruder in turn to obtain mixed masterbatch; 2) Outer sheath material: The mixed masterbatch is added into a preheated single screw extruder and extruded onto the steel belt armor. After cooling in a water bath, the extruded material is fixed and placed in a humid environment at a temperature of 25-40 ℃ for 3-4 days. After the self-crosslinking process of the polyethylene is completed, it is dried to obtain a self-repairing anti-ant cable.
9. A method for preparing a self-repairing anti-ant cable according to claim 8, characterized in that: The parameters of the twin-screw extruder in step 1) are a temperature of 75-165°C and a main engine speed of 190-220 r / min; the parameters of the single-screw extruder in step 2) are a temperature of 170-210°C and a main engine speed of 30-40 r / min.
Citation Information
Patent Citations
Cable-sheath material with self-repair function, preparation method and cable sheath
CN108342048A
Self-repairing rat-proof anti-termite polyurethane, preparation method and application
CN110452355A
Amine oligomer curing agent with hydrogen bond structure and preparation method thereof
CN111253570A
Stretch-resistant insulated cable
CN118852783A
Novel double-layer protection waterproof bus
CN119132709A